Microwave-Assisted Regiospecific Synthesis of Pseudohalohydrin Esters - El Khatib, Mirna; Elagawany, Mohamed; Todadze, Ekaterina; Khelashvili, Levan; El-Feky, Said A.; Katritzky, Alan R. (Synlett, 2012)
N-Acylbenzotriazoles react regiospecifically with epoxides under palladium catalysis to give novel β-(benzotriazol-1-yl)ethyl esters (52–87%) constituting halohydrin ester surrogates.
Keywords: regioselectivity; catalysis; palladium; esters; ring opening